Voices from the periphery : a narrative study of the experiences of sexuality of disabled women in Zimbabwe - Peta, Christine (Department of Health and Rehabilitation Sciences, 2016)
This thesis is located within a conceptual framework which integrates related theoretical concepts under an overarching critical feminist disability studies lens. The study sought to explore within an African context, the experiences of sexuality of 16 disabled women in Zimbabwe by using a narrative methodology. The Biographic Narrative Interpretive Method was used to generate data and a three phased approach to analysing data was used by employing narrative analysis in the first level to produce whole life stories and analysis of narratives at the second level to produce distinctive themes from the stories. The third level of analysis builds on the second level of analysis and in this study it is embedded in the discussion of findings where it represents a latent and deeper layer of analysis which seeks to further understand the data. The findings that emerged from the narrative analysis illuminate the biographic specificity of the experiences of sexuality of disabled women, albeit drawing belief systems from the wider national context. At the second level, the cross-case analysis generated thematic findings which revealed that all participants dynamically engage in intimate partner relationships, albeit being vulnerable to gender based violence, including in matrimonial relationships, in a setting where contextual silences that surround issues of sexuality are detrimental to the well-being of participants. The third level of analysis illuminates the fact that disabled women are not passive recipients of disability and sexuality stereotypes but they claim their agency and create opportunities for themselves in the area of sexuality. Participants value heterosexual marriage in a context where different sexual orientations are despised by culture and same sex marriages are prohibited by the constitution of Zimbabwe. The complex intersection of culture, disability and normative gender roles and power relations within heteronormative relationships facilitate the vulnerability of disabled women to unsafe sexual practices which exacerbate their vulnerability to HIV infection, in a context which is characterised by a lack of sexuality education.